Legal Communication for Gen Z, Disability Groups, and Fishing Communities Through Cultural Da'wah Approach in Jakarta - Dini Wahdiyati; Said Romadlan; Mukhlish Muhammad Maududi; Hendri Prasetya; Gilang Kumari Putra (AMK : Abdi Masyarakat UIKA, 2026)
For some grassroots communities, legal issues are problems that are not widely understood and seem complicated. Therefore, they have gained an understanding of the law, especially related to their rights through legal communication. Because the target of this community service activity is grassroots groups, the approach uses Cultural Da'wah. The cultural da'wah approach is one of Muhammadiyah's da'wah strategies in spreading Islamic teachings by integrating the values of Islamic teachings with local traditions, creatively, persuasively, and humanistically. By using problem-solving methods such as lectures, interactive discussions, and focus group discussions, this activity can provide understanding, awareness, and empowerment regarding legal issues that are often faced by grassroots communities. They understand the legal aspects related to electronic-based sexual violence, the rights of persons with disabilities, the protection and empowerment of fishermen. They are also aware and empowered to deal with the legal problems they face because they already understand the legal and legal aspects related to their respective groups. In conclusion, as a form of cultural da'wah, this activity has very good implications as an effort to understand, awareness, and empower legal issues through legal communication so that they become legally literate and can overcome the legal problems they face.